Narrative and the Reconfiguration of Social Work Ethics - Baldwin, Chris; Estey-Burtt, Brandi (Narrative Works)

(untitled) (The University of New Brunswick, 2012)
Commencing with a critique of codes of ethics based on the Statement of Principles of the International Federation of Social Work, we explore how a narrative approach to ethics might better serve the practice of social work. We argue that narrative both addresses some of the problems within current codes—such as their Western assumptions, lack of attention to the political role of the social worker, and the privileging of professional expertise—and aligns well with the values social work, being committed to social justice and diversity. Furthermore, we suggest that narrative, because it can operate at the individual, family, community, social, and discoursal levels can help us think ethically about how we construct narratives about, with, and for individual service users while remaining attentive to wider concerns of social justice. In so doing we are not seeking to construct a new code of ethics but to generate debate as to how social work ethics might be reconfigured.